Lalla Rookh - Moore, Thomas, 1779-1852; Sulman, T. (Thomas), 1834?-1900; Tenniel, John, 1820-1914 (Salt Lake City, UT : Project Gutenberg, 2025)
"Lalla Rookh: An Oriental romance" by Thomas Moore is a romantic work first published in 1817. The poem follows Princess Lalla Rookh, daughter of Mughal emperor Aurangzeb, as she journeys to marry the King of Bukhara. Along the way, she falls in love with Feramorz, a poet in her entourage who entertains her with four enchanting tales. The work blends a frame narrative with interpolated poems set in sumptuous Eastern settings, exploring themes of love, disguise, and identity in a world of Persian splendor. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Lalla_Rookh
Release date is 2025-09-02
Aaron Adrignola, Tim Lindell and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/Canadian Libraries)
Keywords: Love stories; Frame stories; Poets -- Fiction; Storytellers -- Fiction; Orient -- Fiction; Narrative poetry, English